PCR-based evidence showing the presence of Vibrio vulnificus in wound infection cases in Mangaluru, India. (March 2018) - D'Souza, Caroline; Kumar, Ballamoole Krishna; Kapinakadu, Sachidananda; Shetty, Ranjith; Karunasagar, Indrani; Karunasagar, Iddya
Highlights: PCR-based detection of Vibrio vulnificus from wound infections in Mangaluru, India is reported. The V. vulnificus detected in this study belongs to the vcg- C type. The clinical applicability of PCR for the detection of V. vulnificus in clinical cases is highlighted. Abstract: Vibrio vulnificus is a Gram-negative, opportunistic human pathogen capable of causing life-threatening septicaemia, wound infections, and gastroenteritis, especially in immunocompromised individuals. Two cases of V. vulnificus -associated wound infection occurring in diabetic patients are reported here. The pathogen was detected by PCR targeting species-specific marker gyr B and virulence markers, including repeats in toxin ( rtx A) and hemolysin ( vvh A), but the causative agent could not be cultured. Genotyping based on the virulence-correlated gene revealed that the V. vulnificus detected in this study belonged to the vcg- C type, which is commonly associated with clinical cases. This report highlights the clinical applicability of PCR-based methods in the detection of V. vulnificus in culture-negative cases. Such methods may add a very useful clinical dimension to currently used diagnostic practices.